Suppression of ferromagnetic order by Ag-doping: a neutron scattering investigation on Ce2(Pd1−xAgx)2In (x = 0.20, 0.50). (8th June 2018) - Martinelli, A; Giovannini, M; Sereni, J G; Ritter, C
Abstract: The ground state magnetic behaviour of Ce2 (Pd0.8 Ag0.2 )2 In and Ce2 (Pd0.5 Ag0.5 )2 In, found in the ferromagnetic branch of Ce2 Pd2 In, has been investigated by neutron powder diffraction at low temperature. Ce2 (Pd0.8 Ag0.2 )2 In is characterized by a ferromagnetic structure with the Ce moments aligned along the c -axis and values of 0.96(2) µ B . The compound retains the P 4/ mbm throughout the magnetic transition, although the magnetic ordering is accompanied by a significant decrease of the lattice strain along [0 0 l ], suggesting a magnetostructural contribution. The magnetic behaviour of Ce2 (Pd0.5 Ag0.5 )2 In is very different; this compound exhibits an extremely reduced magnetic scattering contribution in the diffraction pattern, that can be ascribed to a different kind of ferromagnetic ordering, with extremely reduced magnetic moments ( 0.1 µ B ) aligned along [0 l 0]. These results point to a competition between different types of magnetic correlations induced by Ag-substitution, giving rise to a magnetically frustrated scenario in Ce2 (Pd0.5 Ag0.5 )2 In.